2009
DOI: 10.1007/s10549-009-0613-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and comprehensive characterization of large genomic rearrangements in the BRCA1 and BRCA2 genes

Abstract: Large genomic rearrangements are estimated to account for approximately 5-10% of all disease-causing mutations in BRCA1 and BRCA2 genes in patients with hereditary breast and ovarian cancer syndrome (HBOC). We use MRC-Holland Multiplex Ligation-dependent Probe Amplification (MLPA) to screen for such rearrangements in patients with HBOC and as a first step in our genetic testing workflow. The technique was applied to a set of 310 independent patients and detected eight different copy number alterations, corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 32 publications
(48 reference statements)
1
34
0
1
Order By: Relevance
“…19,20 These samples were analyzed in subsequent runs mixed with samples without LGRs. In summary, all LGRs were detected (Figure 3 and Supplementary Figure 6B), duplications showed normalized amplicon values above 1.3 and deletions showed values below 0.7.…”
Section: Large Rearrangements Detectionmentioning
confidence: 99%
“…19,20 These samples were analyzed in subsequent runs mixed with samples without LGRs. In summary, all LGRs were detected (Figure 3 and Supplementary Figure 6B), duplications showed normalized amplicon values above 1.3 and deletions showed values below 0.7.…”
Section: Large Rearrangements Detectionmentioning
confidence: 99%
“…The high proportion of LGRs detected in the Hispanic population of the USA can be explained by a single founder deletion of exons 9-12 [41]. In Spain, the frequency of LGRs affecting the BRCA1/2 genes has been estimated at around 2% in BRCA1 and 1.5% in BRCA2 in cases previously testing negative for BRCA1/2 point mutations [42]. In Asian populations, LGRs account for 3% of case in Singapore [43] and 0.8% in Korea [44].…”
Section: Large Genomic Rearrangementsmentioning
confidence: 99%
“…In relation to point mutations in BRCA1 and BRCA2 in Chilean breast cancer families, it was found that 40% of mutations detected are from Spanish origin [5], being recurrent mutations in the population. In relation to LGRs in BRCA1 found in the Spanish population, the reports describe mainly deletions [33][34][35][36] and few duplications. Among duplications one study reported an extra copy of exon 20 in BRCA1 [33], but no segregation or other analysis were performed in order to determine the pathologic relevance of this duplication.…”
Section: Discussionmentioning
confidence: 99%